2021
DOI: 10.1039/d0cc08420d
|View full text |Cite
|
Sign up to set email alerts
|

Covalent capture and electrochemical quantification of pathogenic E. coli

Abstract: Pathogenic E. coli pose a significant threat to public health by causing both foodborne illness and urinary tract infections. A sensitive electrochemical method to detect these pathogens can be used for surveillance and to prevent illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…However, clever detection schemes combined with new platform technologies could help to decrease the time for detection and increase specificity. My group, for instance, works on developing electrochemical sensors to detect infectious disease agents by harnessing the inherent activity of microbes to capture them on an electrode surface (Fig 2; Klass et al , 2021); improving electrodes for detection by decreasing their cost and difficulty of manufacture (Zamani et al , 2021c); and incorporating biological amplification to increase selectivity and sensitivity (Zamani et al , 2021b). Our ultimate goal is to improve global health equity by decreasing the financial barriers to testing (Sofen & Furst, 2020; Castle et al , 2021; Zamani et al , 2021b).…”
Section: New Applications For Electrochemical Biosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, clever detection schemes combined with new platform technologies could help to decrease the time for detection and increase specificity. My group, for instance, works on developing electrochemical sensors to detect infectious disease agents by harnessing the inherent activity of microbes to capture them on an electrode surface (Fig 2; Klass et al , 2021); improving electrodes for detection by decreasing their cost and difficulty of manufacture (Zamani et al , 2021c); and incorporating biological amplification to increase selectivity and sensitivity (Zamani et al , 2021b). Our ultimate goal is to improve global health equity by decreasing the financial barriers to testing (Sofen & Furst, 2020; Castle et al , 2021; Zamani et al , 2021b).…”
Section: New Applications For Electrochemical Biosensorsmentioning
confidence: 99%
“…We developed an electrochemical sensor to detect E. coli from complex food samples and body fluids by covalent capture of the microbes at the electrode surface (Klass et al , 2021). The overall workflow involves the addition of a synthetic amino acid to a sample.…”
Section: New Applications For Electrochemical Biosensorsmentioning
confidence: 99%
“…Furthermore, biosensors have been developed to identify viruses and bacteria. Electrochemical biosensors utilize changes in electrical properties to determine the presence or absence of an analyte of interest (Figure B,C). The detection of intact viruses could provide a simple way to test multiple specimens without extensive sample processing. Using an optofluidic-nanoplasmonic sensor, Yanik et al demonstrated the use of plasmonic nanoholes and pathogen-specific antibodies to gather measurable transmission information to identify viral loads.…”
Section: Detection Of Known and Unknown Pathogensmentioning
confidence: 99%
“…Recently, a functional electrochemical sensor was reported to detect pathogenic strains of Escherichia coli , 37 which are the most common cause of urinary tract infections (UTIs) 38 , 39 and are a major contributor to foodborne illnesses. 40 43 Antibody- and aptamer-based electrochemical sensors have been reported to monitor these pathogens, with detection limits as low as 10 colony-forming units (CFU)/mL.…”
Section: Detecting Emerging Pathogens Electrochemicallymentioning
confidence: 99%